The Alcatraz escape - Bertman, Jennifer Chambliss (Bertman, Jennifer Chambliss. Book scavenger, 2018)
Legendary literary game-maker Garrison Griswold is back in action, this time with "Unlock the Rock." For his latest game, Griswold has partnered with the famous--and famously reclusive--mystery writer Errol Roy to plan an epic escape room challenge on Alcatraz Island. Emily and James are eager to participate, but the wave of fame they are riding from their recent book-hunting adventures makes them a target. Threatening notes, missing items, and an accident that might not have been an accident have the duo worried that someone is trying to get them out of the game at any cost. When Emily's brother is caught red-handed and blamed for all the wrong doings, Emily is certain Matthew is being framed. With Matthew's record on the line, Emily and James can't afford to leave this mystery uncracked.